Three‐dimensional attenuation model of Sierra Negra Volcano, Galápagos Archipelago. Issue 12 (30th June 2016) - Rodd, Rebecca L.; Lees, Jonathan M.; Tepp, Gabrielle
Abstract: The shallow magma system beneath Sierra Negra was imaged using attenuation tomographic methods. The t ∗ spectral decay method for P wave phases was used to highlight regions of high Q p − 1 which suggest the presence of magma melt. High‐ Q p − 1 anomalies ranging from 0.005 to 0.04 are concentrated below the caldera from 0.5 to 10.5 km depths. Attenuation is sensitive to temperature and fluid presence; thus, this high attenuation is interpreted as possible zones of magma accumulation. An imaged shallow body is consistent with geodetic studies on caldera deformation that modeled a magma sill or flattopped diapir of unknown thickness at ∼1 km depth below sea level. Key Points: t* spectral decay method was used to obtain attenuation structure beneath Sierra Negra High‐attenuation anomaly from 0.5 to 10.5 km depth interpreted as possible magma accumulation zones Results support a shallow magma body described and modeled in caldera deformation studies